Initiating decision‐making in neurology consultations: 'recommending' versus 'option‐listing' and the implications for medical authority. Issue 6 (2nd April 2013) - Toerien, Merran; Shaw, Rebecca; Reuber, Markus
Abstract: This article compares two practices for initiating treatment decision‐making, evident in audio‐recorded consultations between a neurologist and 13 patients in two hospital clinics in the UK. We call these 'recommending' and 'option‐listing'. The former entails making a proposal to do something; the latter entails the construction of a list of options. Using conversation analysis (CA), we illustrate each, showing that the distinction between these two practices matters to participants. Our analysis centres on two distinctions between the practices: epistemic differences and differences in the slots each creates for the patient's response. Considering the implications of our findings for understanding medical authority, we argue that option‐listing – relative to recommending – is a practice whereby clinicians work to relinquish a little of their authority. This article contributes, then, to a growing body of CA work that offers a more nuanced, tempered account of medical authority than is typically portrayed in the sociological literature. We argue that future CA studies should map out the range of ways – in addition to recommending – in which treatment decision‐making is initiated by clinicians. This will allow for further evidence‐based contributions to debates on the related concepts of patient participation, choice, shared decision‐making and medical authority.